2007
DOI: 10.1021/tx6003453
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Protein Expression and Carbonyl Content in N,N-Diethlydithiocarbamate Myelinopathy

Abstract: Human exposure to dithiocarbamates results from their uses as pesticides, in manufacturing and as pharmaceutical agents. Neurotoxicity is an established hazard of dithiocarbamate exposure and has been observed in both humans and experimental animals. Previous studies have shown that the neurotoxicity of certain dithiocarbamates, including N,N-diethyldithiocarbamate (DEDC), disulfiram, and pyrrolidine dithiocarbamate can manifest as a primary myelinopathy of peripheral nerve. Because increased levels of copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Previous proteomic investigations of peripheral nerve have shown the greatest increases in protein expression to be associated with members of the IgG class (Viquez et al, 2007). In particular IgG2a demonstrated increases greater than six fold.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous proteomic investigations of peripheral nerve have shown the greatest increases in protein expression to be associated with members of the IgG class (Viquez et al, 2007). In particular IgG2a demonstrated increases greater than six fold.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported increased levels of copper and lipid oxidation to be associated with dithiocarbamate induced neurotoxicity (Calviello, 2005;Delmaestro, 1995;Tonkin, 2004) and correlative data have shown a relationship between copper levels in peripheral nerve and the severity of myelin injury produced by pyrrolidine dithiocarbamate and N,Ndiethyldithiocarbamate (DEDC) in rodent models (Valentine et al, 2006;Valentine et al, 2007). Additionally, proteomic analysis of sciatic nerve proteins using this animal model has demonstrated significant elevations in expression levels of glutathione transferase isozymes within Schwann cells consistent with activation of the antioxidant response element pathways subsequent to DEDC exposure (Viquez et al, 2007). These observations coupled with the affinity of dithiocarbamates for copper have led to the hypothesis that dithiocarbamates bind copper and generate a lipophilic complex that accumulates and promotes lipid oxidation within myelin membranes leading to a subsequent myelinopathy.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A previous study also found a trend toward elevation of zinc in the liver of DEDC treated rats (12), however, no treatment related lesions in the liver or elevations in aspartate amino transferase were found in any of the animals examined. Previous studies have demonstrated that elevations in lipid peroxidation and protein expression levels of antioxidant enzymes in peripheral nerve accompanied DEDC administration (14, 32). Increased expression of glutathione transferase isoforms has been detected in nerve by proteomic analyses; and the observation that elevations of peripheral nerve MDA and F 2 -isoprostanes preceded the onset of lesions suggested that lipid peroxidation could contribute to the development of myelin lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Higher protein carbonyls levels were found, for instance, in corkwing wrasse (Symphodus melops) captured near a disused copper mine where water and sediments are contaminated with heavy metals [44]. Also, copper accumulation and oxidative damage have been linked to toxicity of dithiocarbamate fungicides in rats [45,46].…”
Section: Copper (Cu)mentioning
confidence: 99%